Conflito entre acionistas, concentração acionária, governança corporativa e valor da empresa um estudo nas companhias abertas brasileiras - Patrícia Antonacci Neves (2015)
The relationship between shareholders is full of conflicting interests, which can be caused by numerous factors. The theoretical platform that guided this work was based primarily on Silveira (2002), Dey (2008) and Renders and Gaeremynck (2012), who consider the ownership concentration and corporate governance as the main cause of conflicts between shareholders, whose effects reflect on firm value. This study use a theoretical, empirical, descriptive and quantitative approach and aimed to study the relationship between shareholders conflict, ownership concentration and corporate governance, also relating these variables with the value of the company. The sample consists in 250 public companies listed in 4 indices of the BM&FBovespa in the years of 2012, 2013 and 2014. It was used the principal component analysis in order to create indicators for "conflict", "ownership concentration" and "corporate governance", and the Tobins Q as a proxy to represent firm value. The indicators created were standardized and implemented in fixed and marginal regression models and adjusted for panel data, which used as the dependent variable "conflict" and "firm value". The chosen methods and validation tests of the models confirmed the predictive ability of the marginal models, who could explain 51.7% of the variability of "conflict" and 33.7% of the variability of "firm value." Thus, a significant and positive relation of "ownership concentration" on the "conflict" and significant and negative relation of "corporate governance" on the "conflict" was found. Regarding "firm value" the same variables were not significant. Subsequently, we carried out a cluster analysis, which separated the companies of the sample into 4 groups and related according to the means of "conflict" and "firm value." This analysis confirmed the inverse relationship between this two variables in the sense that companies with higher value, were those who had the lowest average of conflict, while companies with lower value, were the ones that had the highest average of conflict.